Inducing awe with nature videos: Effects on hope, stress, and social connectedness - Yoe, Jennifer (2024)
This study explored the potential of awe-inducing nature videos to elicit positive mental health outcomes. Building on prior research linking natural environments to awe, the study focused on elements of vastness and accommodation inherent in awe-inducing stimuli. Using nature videos, this study aimed to determine if these could induce awe comparable to real-life experiences and whether such awe was associated with reduced stress, increased hope, and motivation to foster social connections. Participants (N = 102) from Prolific were randomly assigned to view either an awe-inducing video a neutral video. Standardized measures assessed awe, stress, hope, and social connection motivation post-viewing. Results revealed that participants exposed to the awe-inducing video reported significantly greater awe (M = 4.171, SD = 1.294) than those in the control group (M = 2.780, SD = 1.100), t(99) = -5.836, p < .001, with a large effect size (d = -1.164). However, there were no significant differences in stress between the awe-inducing video (M = 5.021, SD = 2.279) and control (M = 5.755, SD = 2.800) conditions, t(98) = 1.425, p = .157. Similarly, motivation to foster social connections was not significantly different between groups (Awe: M = 4.311, SD = 1.506; Control: M = 4.563, SD = 1.601), t(99) = 0.812, p = .419. Although hope did not differ significantly between conditions (Awe: M = 5.128, SD = 1.484; Control: M = 5.583, SD = 1.438), t(99) = 1.565, p = .121, awe significantly mediated the relationship between video condition and hope, suggesting that the increase in awe was crucial for the positive effect of the awe-inducing video on hope (indirect effect: b = 0.489, SE = 0.234, 95% CI [0.097, 1.003]). These findings highlight the use of nature videos to induce awe and the role of awe in enhancing hope.